2021
DOI: 10.3390/colloids6010002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water and Salt on the Colloidal Stability of Latex Particles in Ionic Liquid Solutions

Abstract: The colloidal stability of sulfate (SL) and polyimidazolium-modified sulfate (SL-IP-2) latex particles was studied in an ionic liquid (IL) of ethylammonium nitrate (EAN) and its water mixtures. Aggregation rates were found to vary systematically as a function of the IL-to-water ratio. Repulsive electrostatic interactions between particles dominated at low IL concentrations, while they were significantly screened at intermediate IL concentrations, leading to destabilization of the dispersions. When the IL conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…However, 8-4-8, 12-4-12, and 12-6-12 GSs show more complicated behavior, featuring the characteristic U-shaped stability plot, which has been reported for several particle systems containing oppositely charged polyelectrolytes or surfactants. 15 , 16 , 40 , 48 , 49 The SL dispersions were stable at low surfactant concentrations, as indicated by the fairly high stability ratio values determined in this regime. Then, with increasing surfactant amount, the stability ratios decreased and reached a minimum, followed by an increase at higher concentrations, where stable samples were observed.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…However, 8-4-8, 12-4-12, and 12-6-12 GSs show more complicated behavior, featuring the characteristic U-shaped stability plot, which has been reported for several particle systems containing oppositely charged polyelectrolytes or surfactants. 15 , 16 , 40 , 48 , 49 The SL dispersions were stable at low surfactant concentrations, as indicated by the fairly high stability ratio values determined in this regime. Then, with increasing surfactant amount, the stability ratios decreased and reached a minimum, followed by an increase at higher concentrations, where stable samples were observed.…”
Section: Resultsmentioning
confidence: 80%
“…A second-order cumulant fit was applied to the correlation function to determine the hydrodynamic radius (R h ). 38 For the early stages of aggregation, the absolute aggregation rate constant (k) was calculated from the initial change of the R h as a function of time (t) as follows 39,40…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the charge and aggregation tendencies by altering the SL-to-IP-2 ratio in the samples, it can be stated that the dispersions are unstable near the IEP, while sufficiently charged particles below and above the IEP are more stable. These results imply that the IP-2 dose-dependent colloidal stability of SL can be interpreted with the classical DLVO (Derjaguin, Landau, Verwey and Overbeek) theory [54][55][56][57], which predicts that the overall interparticle forces are determined by the sum of repulsive electrical double layer and attractive van der Waals forces. Indeed, rapid aggregation is observed in the present system near the IEP, under which conditions the van der Waals attractive forces predominate over the weak or even vanished repulsive forces otherwise originating from the overlapping electrical double layers.…”
Section: Development Of Sl-ip-2 Particlesmentioning
confidence: 67%
“…These studies have shown that the mechanisms underlying particle stability and aggregation are very different in diluted and concentrated ILs. [82][83][84][85] Indeed, the DLVO theory describes well the behavior of particle dispersions in diluted ILs, and hence, electrostatic interactions mainly determine particle stability in this regime. 85 In contrast, viscous and solvation forces explain particle stability in concentrated and pure ILs, and no evidence was found for the action of a long-range electrostatic repulsion between the particles.…”
Section: Discussionmentioning
confidence: 99%